Evaluation of left ventricular flow field changes after stress in patients with nonobstructive coronary artery disease using ultrasonic flow vector imaging - Li, Dongmei; Zhao, Xin; Xiao, Qiuyu; Yang, Rui; Li, Zizhuo; Xie, Yuanyuan; Mao, Xinyue; Li, Xi; Hu, Wenhan; Deng, Yan (Frontiers in Cardiovascular Medicine, 2024)
Purpose Vector flow mapping and treadmill exercise stress echocardiography were used to evaluate and explore changes in the left ventricular (LV) flow field of patients with nonobstructive coronary artery disease. Methods Overall, 34 patients with nonobstructive (<50%) left anterior descending coronary artery stenosis (case group) and 36 patients with no coronary artery stenosis (control group) were included. Apical four-, three-, and two-chamber echocardiographic images were collected at rest and during early recovery from treadmill exercise. LV flow field, vortex area, and circulation (cir) changes were recorded in different phases: isovolumetric systole (S1), rapid ejection (S2), slow ejection (S3), isovolumetric diastole (D1), rapid filling (D2), slow filling (D3), and atrial systole (D4). Intra- and inter-group differences were compared before and after exercise loading. Results The control and case groups demonstrated regular trends of eddy current formation and dissipation at rest and under stress. Compared with the control group, the case group had irregular streamline distributions. Abnormal vortices formed in the S1 and D3 apical segments and D1 left ventricular middle segment in the resting group. Compared with the control group, the resting group had decreased left ventricular S1 vortex areas and increased S3 vortex areas. The post-stress D1 and D3 vortex areas and D1 and D2 cir increased. Compared with at rest, after stress, the control group had decreased S1, S3, D2, and D3 vortex areas; increased S2, D1, D3, and D4 cir; and decreased D2 cir. After stress, the case group had decreased S3 and D2 vortex areas, increased D1 vortex areas, and increased S2, D1, D3, and D4 cir (P all < 0.001). Logistic regression and ROC curve analyses show that increased D1 vortex area after stress is an independent risk factor for stenosis in nonobstructive stenosis of coronary arteries (OR: 1.007, 95% CI: 1.005–1.010, P < 0.05). A D1 vortex area cutoff value of 82.26 had an AUC, sensitivity, and specificity of 0.67, 0.655, and 0.726, respectively. Conclusion The resting left ventricular flow field changed in patients with nonobstructive left anterior descending coronary artery stenosis. Both groups had more disordered left ventricular blood flow after stress. The increased D1 vortex area after stress is an independent risk factor for mild coronary stenosis and may contribute to the assessment of nonobstructive coronary stenosis. VFM combined with treadmill stress is useful in evaluating left ventricular flow field changes in patients with nonobstructive coronary artery disease, which is valuable in the early evaluation of coronary heart disease.